Integration of in vitro and in silico approaches to assess three Astragalus species from Turkey flora: A novel spotlight from lab bench to functional applications - Gokhan Zengin; Abdullahi Ibrahim Uba; Mustafa Ocal; Majid Sharifi-Rad; Giovanni Caprioli; Simone Angeloni; Yasemin Celik Altunoglu; Mehmet Cengiz Baloglu; Evren Yıldıztugay (Elsevier BV, 2022)
Members of the genus Astragalus have a great interest as a source of natural bioactive compounds on a scientific platform. To provide multidirectional insights into three Astragalus species (A. setulosus, A. anthylloides, and A. ovalis), the current work focused on the chemical characterization and biological properties of their extracts (aerial parts and roots). The chemical characterization of the extracts was detected by HPLC-MS/MS analysis. The biological properties were evaluated by antioxidant, enzyme inhibitory, and cytotoxic parameters. Assays for radical quenching, reducing capacity, and metal chelation were also used to evaluate antioxidant properties. To test the enzyme inhibitory effects of the extracts, cholinesterases, tyrosinase, alpha-amylase, and alpha-glucosidase were utilized as target enzymes. Two cancer cell lines, (MCF-7 (human breast cancer cell line) and HeLa (Human cervix cancer cell line), were selected to evaluate cytotoxic effects. Generally, 5- caffeoylquinic acid (2.43-283.92 mu g/g extract), hyperoside (4.33-216.22 mu g/g extract) and rutin (1.09-184.98 mu g/g extract) were the main constituents. The extracts from aerial parts and roots of A. anthylloides showed stronger radical scavenging and reducing power abilities compared to A. setulosus and A. ovalis. The best AChE and BChE inhibitory effects were determined in the aerial parts of A. setulosus (2.18 mg GALAE/g) and mots of A. ovalis (4.76 mg GALAE/g), respectively. The extracts of A. ovalis had the highest tyrosinase inhibitory abilities. The extract from aerial parts of A. setulosus showed stronger cytotoxic effects compared to other extracts. Pearson's correlation analysis revealed that the presence of some compounds (resveratrol, p-coumaric, 5-caffeoylquinic, and ferulic acids, etc) was linked to the observed biological activities. Molecular docking was also provided for the possible interaction of enzymes as well as protein targets of the tested cell lines. Our findings provide a scientific basis for the Astragalus species, which may serve as a source of naturally occurring bioactive compounds for health-promoting applications.
Keywords: Inhibitors; Astragalus; Cytotoxic effect; P-Coumaric Acid; Antioxidant Activity; Membranaceus; Chemical-Composition; Expression; Alzheimers; Bioactive agents; Molecular docking; Leguminosae; Profile; Breast-Cancer; Phenolics; 3. Good health